2020
DOI: 10.3390/su12208439
|View full text |Cite
|
Sign up to set email alerts
|

Necessary Conditions for Multi-Domain Indoor Environmental Quality Standards

Abstract: A discussion of sustainability in architecture cannot be meaningfully carried out without the inclusion of most buildings’ central purpose, namely the provision of indoor environments that are accommodating of occupants’ needs and requirements. To this end, building designers and operators are expected to demonstrate compliance with codes and standards pertaining to indoor environmental quality (IEQ). However, the majority of conventional IEQ standards, codes, and guidelines have a single-domain character, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, as illustrated in Figure 1, common systems for building rating and certification (e.g., [14,15]) appear not to entail explicit specifications of indoorenvironmental requirements. Rather, they tend to refer to other thematically related national or international standards such as ISO, EN, DIN, or ANSI [1]. Some of these standards (e.g., DIN EN 15251) refer, in turn, to other standards.…”
Section: In Search Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…However, as illustrated in Figure 1, common systems for building rating and certification (e.g., [14,15]) appear not to entail explicit specifications of indoorenvironmental requirements. Rather, they tend to refer to other thematically related national or international standards such as ISO, EN, DIN, or ANSI [1]. Some of these standards (e.g., DIN EN 15251) refer, in turn, to other standards.…”
Section: In Search Of Evidencementioning
confidence: 99%
“…Figure 4 schematically illustrates the elements of such indoor-environmental comfort equations. Thereby, a set of physical variables is intended to formulate dependent variables that capture building users' level of comfort [1]. Whereas physical variables can be typically derived by measurements, dependent variables result from subjective evaluations.…”
Section: Sources Of Indoor-environmental Comfort Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that, although the metrics are clearly defined, there is no clear methodology for benchmarking and correlating those metrics with occupants' subjective responses. Mahdavi et al reviewed current state-of-art IEQ evaluation approaches and indicated that existing approaches tend to be mono-dimensional, and people's evaluation of the IEQ are often overlooked (Mahdavi et al 2020).…”
Section: Overview Of the Existing Building Performance Metricsmentioning
confidence: 99%
“…Building standards and guidelines regarding human comfort commonly address indoorenvironmental requirements in isolation (Mahdavi et al, 2020a). However, typical indoor environments, such as office settings, are multi-dimensional and include a multitude of indoorenvironmental factors (e.g., thermal, auditory, visual, and air quality conditions).…”
Section: Introduction Motivation and Backgroundmentioning
confidence: 99%